PEMANFAATAN LARVA BLACK SOLDIER FLY DALAM PEMBUATAN BAHAN DASAR PAKAN AYAM - Naniek Ratni JAR; Putri Maria Dermawati Allagan (EnviroUS, 2022)
Waste that is processed properly will create a new energy that can be reused without having to damage the environment. One way is to use Black Soldier Fly (BSF) larvae in processing organic waste. The purpose of this study was to determine the effect of food waste and mixed waste of mustard greens and cabbage on the growth of BSF larvae and to compare the quality of BSF larvae content as a basic ingredient of chicken feed. In this study, BSF larvae were used in organic waste media with a life span of 5 days. With variations in the distribution of waste, namely, 500gr, 1000gr, 1500gr, 2000gr, and 2500gr. In food waste, there was an effect on larval growth in the 1000gr variation, which was around 678.84% and in mixed vegetable waste, there was an effect on larval growth in the 1000gr variation, which was about 579.4%. And the BSF larvae using this organic waste have a protein content value that exceeds 30% and fat by 37% so that it meets the content standards regulated in SNI 7783.2.2013, namely the standard for native chicken feed.